2022
DOI: 10.4102/hsag.v27i0.1984
|View full text |Cite
|
Sign up to set email alerts
|

Management of epilepsy through indigenous traditional and Western approaches in Africa: A systematic review

Abstract: Background: Reaction to epilepsy management has been described as moulded by traditional beliefs, despite the reported progress of anti-epilepsy medication. In Africa, traditional healers are seen as essential in providing epilepsy care, yet little is known about their epilepsy care.Aim: This manuscript aimed to systematically review and summarise the various indigenous traditional and Western methods of epilepsy management and their effectiveness in Africa.Setting: This study is conducted in Africa.Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The challenge of treatment attainment poses a significant obstacle for individuals seeking effective care. [18][19][20] The study participants reported difficulties accessing medication and sometimes experienced its ineffectiveness. Despite these challenges, a majority of participants expressed a preference for Western treatment options over faith-based treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge of treatment attainment poses a significant obstacle for individuals seeking effective care. [18][19][20] The study participants reported difficulties accessing medication and sometimes experienced its ineffectiveness. Despite these challenges, a majority of participants expressed a preference for Western treatment options over faith-based treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural beliefs may lead to stigmatization and discrimination against people with epilepsy, affecting their quality of life. Moreover, some traditional practices, such as restrictive and dangerous restraint methods, can be harmful and even life‐threatening to people with epilepsy 23 . Therefore, it is critical to raise awareness about the negative impacts of cultural beliefs and practices and promote the adoption of evidence‐based management strategies to ensure safe and effective treatment for people living with epilepsy in Africa.…”
Section: Cultural Socioeconomic and Healthcare Factors Affecting Epil...mentioning
confidence: 99%